Endovascular embolization for basal ganglia and thalamic arteriovenous malformations - Lan, Jing; Ma, Yi-hui; Feng, Yu; Zhang, Ting-Bao; Zhao, Wen-yuan; Chen, Jin-cao (Frontiers in Neurology, 2023)
Background Basal ganglia and thalamic arteriovenous malformations (AVMs) represent a special subset of malformations. Due to the involvement of vital brain structures and the specifically fine and delicate angioarchitecture of these lesions, it presents unique therapeutic challenges and technical difficulties that require thorough treatment planning, individualized treatment strategies, and advanced techniques for good clinical outcome. Method In this study, we presented a series of ruptured basal ganglia and thalamic AVMs embolized via a transarterial, transvenous or combined approach. Herein, we summarized our treatment experience and clinical outcomes to further evaluate the effectiveness and safety of endovascular embolization for these AVMs as well as the indications, therapy strategies, and techniques of embolization procedures. Results Twelve patients with basal ganglia and thalamus AVMs were included in the study. Their average age was 23.83 ± 16.51 years (range, 4–57 years) with a female predominance of 67% at presentation. The AVMs were located in the thalamus in 3 (25%) patients, in the basal ganglia in 3 (25%) patients, and in both sites of the brain in 6 (50%) patients. There were 5 AVMs located on the left side and 7 on the right. The mean nidus diameter was 3.32 ± 1.43 cm (range 1.3–6.1 cm). According to the Spetzler-Martin grading classification, 4 (33.3%) brain AVMs were Grade III, 7 (58.3%) were Grade IV, and 1 (8.3%) was Grade V. All of them presented with bleeding at admission: four of these patients presented with an intracerebral hemorrhage (ICH), 8 ICH in combination with intraventricular hemorrhage (IVH), and no patient with subarachnoid hemorrhage (SAH). Among these patients treated with endovascular embolization, 7 patients were treated by the transarterial approach, 4 patients transvenous approach, and 1 patient underwent the combined approach. A single embolization procedure was performed in 6 patients (50%) and the other 6 cases (50%) were treated in a staged manner with up to three procedures. Procedure-related complications occurred only in two patient (16.7%). Complete AVM obliteration was obtained in 7 patients (58.3%), and partial obliteration was in 4 patients (33.3%). Overall, good or excellent outcomes were obtained in 7 patients (58.3%), and poor functional outcome was observed in 5 patients (41.7%) at the last follow-up. All survived patients achieved anatomic stabilization and there was no postoperative bleeding or recurrence in the follow-up. Conclusion The management of the basal ganglia and thalamic AVMs is a great challenge, which needs multimodal individualized treatment to improve the chances of radiographic cure and good outcomes. Endovascular therapy is safe and effective in the treatment of cerebral AVMs particularly for deep-seated AVMs such as the basal ganglia and thalamus. Our results demonstrate a high rate of anatomic obliteration with an acceptable rate of complications in the endovascular treatment of these vasculopathies via a transarterial approach or a transvenous approach.